Safety Profile of Paxlovid in the Treatment of COVID-19 - Lv, Bing; Gao, Xin; Zeng, Guoqiang; Guo, Hui; Li, Faping (Current pharmaceutical design, 2024)
With the urgent and widespread application of Paxlovid, a novel antiviral drug for Coronavirus Disease 2019 (COVID-19) in clinical practice, concerns regarding its actual efficacy and safety have emerged. In order to provide more evidence to support its clinical application, we sought to perform a descriptive analysis of cases who experienced at least one Paxlovid-related adverse event (AEs) and reported to the FDA Adverse Event Reporting System (FAERS) in the post-marketing period. Individual adverse event reports between January 1, 2022 and September 30, 2022, were downloaded from the FAERS website. We completed a descriptive study about the safety of Paxlovid in the treatment of COVID-19. Further, we also analyzed the onset time of Paxlovid-related AEs. As of 30 September 2022, 16,529 de-duplicated cases were submitted to the FDA, and 5,860 (35.45%) were female. The average age was 58.38 years (S.D. 15.50). Most reports (12,390, 74.96%) were submitted by consumers and 1,436 (8.68%) concerned serious outcomes. The most frequently reported AEs were disease recurrence (7,724, 16.23%), dysgeusia (2,877, 6.05%), and diarrhoea (1,448, 3.04%). The median onset time of Paxlovid-related AEs was 8 days (interquartile range,1-10 days), and most of the cases (2,629, 19.12%) occurred on the day after Paxlovid initiation. This study indicates that the most common AEs reported with Paxlovid in post-marketing experience are consistent with the safety assessment of antiviral drugs. Even without emerging apparent safety concerns, the incidence of serious outcomes was unexpectedly high, and a few cases of potential new AEs occurred.